2021
DOI: 10.1101/2021.11.22.469622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell dissection of obesity-exercise axis in adipose-muscle tissues

Abstract: Regular physical exercise has long been recognized to reverse the effects of diet-induced obesity, but the molecular mechanisms mediating these multi-tissue beneficial effects remain uncharacterized. Here, we address this challenge by studying the opposing effects of exercise training and high-fat diet at single-cell, deconvolution and tissue-level resolutions across 3 metabolic tissues. We profile scRNA-seq in 204,883 cells, grouped into 53 distinct cell subtypes/states in 22 major cell types, from subcuta-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 112 publications
1
1
0
Order By: Relevance
“…Lastly, we asked whether transcription factors (TFs) contribute to the phenotypic state of these subpopulations (Figure 2H). It is reported that transcriptional diversity decreases during differentiation [27]. Our results con rmed that mA3 and mA4, rather than mA5 showed increased transcriptional diversity, consistent with their earlier differentiation state.…”
Section: Vat Contains Distinct Subpopulations Of Adipocytessupporting
confidence: 84%
“…Lastly, we asked whether transcription factors (TFs) contribute to the phenotypic state of these subpopulations (Figure 2H). It is reported that transcriptional diversity decreases during differentiation [27]. Our results con rmed that mA3 and mA4, rather than mA5 showed increased transcriptional diversity, consistent with their earlier differentiation state.…”
Section: Vat Contains Distinct Subpopulations Of Adipocytessupporting
confidence: 84%
“…Our studies suggest that many more cell types respond to exercise than previously recognized, including Pdgfra + cells distributed to multiple organ systems. Recent reports using single cell RNA-sequencing showed that exercise regulation in adipose was most strongly pronounced in adipose stem cells (Yang et al, 2021), which are defined by the expression of Pdgfra + (Shin et al, 2020). These adipose-resident fibroblasts may indeed correspond to a subset of the Pdgfra + cells identified in our secretome profling dataset.…”
Section: Discussionmentioning
confidence: 99%